Comparing distributed memory and virtual shared memory parallel programming models - Keane, J.A.; Grant, A.J.; Xu, M.Q. (Future generation computer systems, 1995)
The virtues of the shared memory and distributed memory parallel programming models have been much debated. Conventionally the debate could be reduced to programming convenience on the one hand, and high scalability factors on the other. More recently the debate has become somewhat blurred with the provision of virtual shared memory models built on machines with physically distributed memory. The intension of such models/machines is to provide scalable shared memory, i.e. to provide both programmer convenience and high scalability. In this paper, the different models are considered from experiences gained with a number of systems ranging from applications in both commerce and science to languages and operating systems. Case studies are introduced as appropriate.